Research Paper: Sex Determination Based on Radiographic Examination of Metatarsal Bones in Iranian Population - Akhlaghi, Mitra; Bakhtavar, Khadijeh; Bakhshandeh, Hooman; Mokhtari, Tahmineh; Vasheghani Farahani, Maryam; Allahyar Parsa, Vida; Mehdizadeh, Farzaneh; Sadeghian, Mohammad Hossein (International Journal of Medical Toxicology and Forensic Medicine, 2017)
Background: In forensic medicine, sex can be determined by studying human skeletal remains. This study aimed to evaluate the reliability of metatarsal bones in sex determination in Iranian population. Methods: A total of 184 healthy individuals (103 males and 81 females) were enrolled in the study. The sample was divided into three age groups: 20-34, 35-49, and ≥50 years. The length, width, length to width ratio (L/W), and length by width (L×W) product of sample’s right foot metatarsal bones were measured using their radiographic images. Results: The differences of length, width, L/W ratio, and L×W between two sexes were significant in all age groups (P<0.001). First metatarsal L×W had sensitivity and specificity of 85.4% and 88.8%, respectively, but the mean total L×W value of metatarsal bones had sensitivity and specificity of 94.2% and 78%, respectively. Conclusion: The first and the mean L×W values of all metatarsal bones had the highest accuracy for discriminating sexes (86.9% and 85.2%). The first metatarsal width and mean width of all metatarsal bones had an accuracy of 82.6% and 84.2%, respectively. In forensic medicine, these indexes can be used for sex-differentiation.